Functional plasticity of neutrophils after low- or high-dose irradiation in cancer treatment – A mini review - Hu, Jing; Pan, Mingyue; Wang, Yixi; Zhu, Yujie; Wang, Meidan (Frontiers in Immunology, 2023)
Over the last several decades, radiotherapy has been considered the primary treatment option for a broad range of cancer types, aimed at prolonging patients' survival and slowing down tumor regression. However, therapeutic outcomes of radiotherapy remain limited, and patients suffer from relapse shortly after radiation. Neutrophils can initiate an immune response to infection by releasing cytokines and chemokines to actively combat pathogens. In tumor immune microenvironment, tumor-derived signals reprogram neutrophils and induce their heterogeneity and functional versatility to promote or inhibit tumor growth. In this review, we present an overview of the typical phenotypes of neutrophils that emerge after exposure to low- and high-dose radiation. These phenotypes hold potential for developing synergistic therapeutic strategies to inhibit immunosuppressive activity and improve the antitumor effects of neutrophils to render radiation therapy as a more effective strategy for cancer patients, through tumor microenvironment modulation.